10031-RT-02 Results of reactor-based BNCT for 44 cases of recurrent and refractory high-grade meningiomas and road to accelerator based BNCT. (28th November 2020) - Miyatake, Shin-Ichi; Kawabata, Shinji; Wanibuchi, Masahiko; Takai, Satoshi; Takeuchi, Koji; Ono, Koji; Ko, Naonori; Sakurai, Yoshinori; Tanaka, Hiroki; Suzuki, Minoru
Abstract: Introduction: High-grade meningioma (HGM) is difficult clinical entity to treat. Especially recurrent HGM after some radiotherapy has very miserable prognosis. For example median overall survival (mOS) of recurrent HGM after radiotherapy is reported as 2 years. We applied tumor-selective particle radiation BNCT using nuclear reactor for 44 recurrent HGMs. Methods: From 2005 to 2019, we treated 44 recurrent and refractory HGMs by reactor-based BNCT. The patients' WHO grades are grade 2:20 cases, grade 3:24 cases. Prior to BNCT, totally 114 times operations and 72 times SRS and 14 times external beam radiotherapy were applied for them. OS, tumor shrinkage, causes of treatment failure were analyzed. Results: Median follow-up was 26.0 months. MOS after BNCT was 29.6 (95% CI:16.1–40.4) months. Grade 2 and 3 showed mOS as 44.4 (27.4-) and 21.55 (10.6–30.6) months, respectively and there is statistically significance (p=0.0009). All treated tumor showed rapid shrinkage on MRI. Treatment failure patterns are local recurrence, out of field recurrence, systemic metastasis, CSF dissemination, as 35.5%, 20.6%, 17.6%, 8.8 %, respectively. These results showed good local tumor control and prolonged survival for recurrent HGM cases. Conclusions: Our cases were heavily treated with repetitive surgeries and repetitive radiotherapy. In addition the rate of grade 3 patients was extremely high. In a word our cases seemed to have poor prognosis. In spite of these poor condition, reactor-based BNCT exerted good local control and prolonged survival for recurrent and refractory HGMs. Depending on the clinical results, PMDA gave us the permission to apply investigator-lead clinical trial for recurrent and refractory HGMs using accelerator-based BNCT with financial support from AMED (one of the agency of Japanese government). In our talk, let us open some results from this trial.